Implementation of Equal Educational Learning at the Community Learning Activities Center (PKBM) Bina Insani Bandung - Santy Christinawati; M. Yusuf Sanny; Siti Saadah; Muchtarom Muchtarom (Universitas Muhammadiyah Enrekang, 2023)
This study aims to describe: 1) Preparation for learning equality education, 2) Supporting factors and inhibiting factors for the implementation of learning equality education. This research is a descriptive research with a qualitative approach. The research results obtained in this study are the application of learning activities at PKBM Bina Insani Bandung based on the 2006 curriculum standards which include: 1) The preparatory stage for learning equality education has been carried out properly. Preparation for learning in the form of compiling a syllabus carried out by tutors is categorized as good, 2) Supporting factors and inhibiting factors for the implementation of equality education learning. The supporting factors are the existence of sufficient infrastructure for the learning process, while the inhibiting factors are the lack of motivation of learning residents to take part in learning at PKBM, the lack of funding sources, the motivation and fighting spirit of PKBM management which is still low, the place is still rented, the facilities and infrastructure are still limited , and the lack of public awareness of the importance of education.